PEMANFAATAN MEDIA TANYA DAN TEMPEL (TAPEL) UNTUK MENINGKATKAN AKTIVITAS SISWA DALAM MATERI MENGENAL NEGARA-NEGARA ASEAN DI KELAS VIII A SMP NEGERI 1 PUHEPELEM SEMESTER GENAP TAHUN PELAJARAN 2022/2023 - Rismiono, Danar (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
This research aims to determine the improvement in social studies learning outcomes by implementing the use of Tapel in Class VIII A of SMP Negeri 1 Puhpelem Semester 1 for the 2022/2023 academic year for the material Getting to Know ASEAN Countries. The data collected through observations and tests on learning outcomes are compiled, explained, and finally analyzed in two stages, namely: Data Reduction and Data Display. In accordance with the provisions in Classroom Action Research, the subjects in this research were students in Class VIII A of SMP Negeri 1 Puhpelem for the 2022/2023 academic year. Class VIII A students were the subjects of this research because based on the results of initial observations, the teacher found a problem in this class, namely the low student learning outcomes in the material Getting to Know ASEAN Countries. The Tapel Method is a method that provides the widest possible opportunity for students to be directly and actively involved in finding solutions to various problems in the learning process, from planning to studying a topic through investigation. Democratic teaching is a learning process that is based on democratic values, namely respect for abilities, upholding justice, implementing equality of opportunity, and paying attention to the diversity of students. The results obtained after carrying out the stages in cycle 1 and cycle 2 were that the use of Tapel had a positive impact on the learning process for social studies subjects, especially on the Concept Material of Getting to Know ASEAN Countries. It can be seen from the comparison of the number of students who completed their studies from pre-cycle to cycle 2, namely that in the pre-cycle there were 7 students who completed their studies, then in cycle 1 it increased to 16 students and in cycle 2 to 18 students. By using teaching aids, it is easier to understand the lessons taught by the teacher.